In-depth insight of thermodynamic and kinetic barrier for computation of nucleation rate and interfacial energy of ultra-small Gd2O3 nanoclusters utilizing non-isothermal thermogravimetric models - Verma V.K.; Sabbarwal S.; Srivastava P.; Kumar M. (My University, 2025)
Determination of temperature-dependent nucleation rate is a crucial parameter to accessing the kinetic and thermodynamic barrier linked with developing subatomic-sized nuclei, which tend to restrain the nucleation process. In this study, we exclusively compute the nucleation rate, thermodynamic parameters, and interfacial energy of ultra-small gadolinium oxide nanoclusters at high temperatures. Here, the apparent value of activation energy (Ea.) and pre-exponential kinetic factor (Aa) was precisely computed by utilizing the most accurate Vyazovkin advanced and KAS iso-conversional method, which was further exploited to estimate the thermodynamic parameters, nucleation rate, and interfacial energy of ∼1 nm-sized gadolinium nanoclusters, in the temperature ranging from 555 to 780 K by appraising thermogravimetric data. The obtained Z (α) master plot suggested the existence of random nucleation within the BSA matrix of Gd2O3 nanoclusters at high temperatures over a specified conversion value. Additionally, four mathematical models were proposed using the above finding to interpret the nucleation rate and interfacial energy concerning high temperature and specified conversion points for the first time. © 2023 IOP Publishing Ltd.